Why Do We Feel Like Intellectual Frauds? A Self-Determination Theory Perspective on the Impostor Phenomenon in Medical Students. Issue 2 (15th March 2023) - Neufeld, Adam; Babenko, Oksana; Lai, Hollis; Svrcek, Clark; Malin, Greg
Abstract: Theory: Impostor phenomenon (IP) refers to people's feelings of intellectual fraudulence and fear of being "discovered, " despite contradicting evidence of success. Due to its association with burnout and distress, it is progressively being studied in medicine. While various explanations for IP have been discussed in the literature, the role of motivation has largely been neglected. Hypotheses: Using self-determination theory (SDT) as a lens, it was hypothesized that different general causality orientations (impersonal, control, autonomy), domain-specific types of motivation (autonomous vs. controlled) toward going to medical school, and levels of satisfaction of basic psychological needs (autonomy, competence, relatedness) in the medical program, would each predict severity of IP symptoms. Method: A total of 1, 450 medical students from three Canadian institutions were invited to complete a survey containing the Clance Impostor Phenomenon Scale and scales derived from SDT's mini theories: basic psychological needs theory, causality orientations theory, and organismic integration theory. We explored the prevalence of IP among the students and used regression to capture variable relationships, accounting for gender effects. Results: Data from 277 (19.1%) students were assessed, 73% of whom reported moderate or worse IP symptoms. Having an impersonal general causality orientation, more controlled motivation toward going to medical school, and lower need satisfaction in the medical program, each related to increased IP severity. Together, these motivational factors accounted for 30.3%, 13.6%, and 21.8% of the variance in students' IP severity, respectively. Conclusions: Findings from this study suggest that students who are more self-determined (both in general and in medical school), and whose basic psychological needs are more supported in their medical program, will experience less frequent and severe IP symptoms. Preliminary explanations and implications of these findings are discussed within the medical education context.